Pulmonary involvement in systemic sclerosis (2016)
Systemic sclerosis (SSc) is a multi-systemic autoimmune disease that mainly affects the skin, lungs, gastrointestinal tract, heart and kidneys. Pulmonary disease in patients with SSc is strongly associated with mortality. The mechanisms involved into its pathophysiology include the activation of autoimmune cells and hyperplasia of fibroblasts with an increased capacity to produce collagen and diminished collagen breakdown. Although pulmonary biopsy is the gold standard for the diagnosis of interstitial lung disease in SSc, the most commonly used method is high-resolution computed tomography due to its high sensitivity and specificity. Herein, a comprehensive review on the pulmonary involvement in SSc is presented highlighting the radiologic–pathologic correlations. © 2016 Elsevier B.V.